Case report of prostatic cancer with metastasis and low PSA level (PSAa, is it still a good marker for prostate adenocarcinoma) - Yaghi, M; Jirásek, Ernest (Abstracts of the 2nd Czech and International Congress of Andrology, 2007)
70 years old man was admitted to Internal medicine department for staging of colorectal Carcinoma and Colonoscopy, on per rectum examination which was performed by surgent. There was a huge mass obstructing the lumen of the rectum, PSA level was 1.14 a year ago. On Computer Tomography, dorsally to the urinary bladder there was a huge nonhomogenic mass sized 11 cm x 9 cm x 10 cm, prostate and seminal vesicles were not differentiated, the mass is leing on the dorsal wall of the urinary bladder, the lumen of rectum is norrowed irregularly and deviated to the right side, the wall of rectum is filled by the patological mass. On Ultrasound there were enlarged retroperitoneal lymph nodes and expanding mass between the prostate and ampulla of rectum. Colonoscopy was performed, there was a Cauliflower-like tumor, fragile and bleeding, filling the ampulla of the rectum, 2 biopsies were taken from the mass during colonoscopy, according to histology there were tumor cells growing into the rectum from the Urogenital tract. Cystoscopy were recommended by the pathologist. Then the patient was transported to our department. We have performed flexible Cystoscopy without distinctive findings, sextant biopsy has been done later. Histology showed that it is prostatic tumorous cells, the PSA was 5.4 at time of diagnosis, according to Imunohistochemistry. It was Desmoplastic Carcinoma of prostate, on Bone scan there were suspecious pathological findings on the right shoulder joint and the head of the left femur, the pacient was sent later to Oncology department for Radiotherapy. Examinations and Radiological findings Abdominal Ultrasound: 1 – Slight Hepatomegaly 2 – Retroperitoneal lymphadenopathy – paraaortal 3 – Parapelvic cysts on both kidneys 4 – Suspected diverticle of Urinary bladder 5 – Expanding mass in pelvis between prostate and ampulla of rectum Lungs x-ray: without pathological findings. CT of pelvis: 1 – Huge Tumorous mass dorsally to the urinary bladder, infiltrating nearby organs 2 – Pelvic and retroperitoneal lymadenopathy 3 – Suspected diverticle of the urinary bladder Colonoscopy: 1 – Cauliflower-like tumor, fragile and bleeding, filling the ampulla of rectum 2 – Internal Hemorrhoids 3 – Diverticulosis of sigmoidal colon Bone Scan: 1 – suspected Tumorous changes in the region of right shoulder joint and the head of left femur 2 – degenarative changes on the spine Histology from rectum: Tumorous cells growing in the rectum from the Urogenital tract.